PENGARUH KOLEKTIVISME, PERCEIVED CONSUMER EFFECTIVENESS, DAN KEPEDULIAN LINGKUNGAN TERHADAP PERILAKU PEMBELIAN RAMAH LINGKUNGAN - Widodo, Tri; Qurniawati, Rina Sari (Jurnal Ilmiah Among Makarti, STIE AMA Salatiga, 2015)
AbstractThese days, most consumers have realized that their purchasing behavior has a direct impact on the incidence of various environmental problems. Consumers adapt to new situations which threaten this by considering environmental issues when they are shopping. There are several factors that make the driving behavior of the community began to show the purchase of products that are environmentally friendly.This research design is the design of a survey conducted in order to test the influence of collectivism, Perceived Consumer Effectiveness (PCE), and Environmental Concern on environmentally friendly purchasing behavior. Survey conducted on 40 respondents with at least one high school.Data analysis was performed using multiple linear regression. The results showed that: 1) collectivism significant influence on the purchasing behavior of environmental friendly; 2) Perceived Consumer Effectiveness (PCE) significant influence on the purchasing behavior of environmental friendly; 3) environmental awareness significant influence on the purchasing behavior of environmental friendly. Keywords : Sustainable Purchasing Behavior, Collectivism, PCE, Environmental Concern, Multiple Linear Regression